Relações entre pares: a perspectiva de um grupo de adolescentes em conflito com a lei - Santos, Cristiane Rosa dos (2013)
This study aims to discover and describe how are established friendly relations among adolescents imprisoned in Center of social and educational rehabilitation of Santa Maria. Will be investigated their experiences and perceptions about the relationships established with peers both inside and outside the institutional context. For that, was conducted a qualitative exploratory study, that used the resource autofotographic combined with semistructured interviews with teenagers in restrictive measure of freedom in times of external activity. The information analysis was performed using the technique of thematic content analysis.The presented results contribute to the understanding aspects related to the characteristics of the people with whom these young people establish friendly relations, in what context these interactions occur and how to organize and develop strategies to support each other. Moreover, it was possible to observe how are experienced relationships with friends and how these are influenced for relations with the enemies. The study showed the importance of thinking about relations in group and adolescence considering the numerous characteristics cultural, psychological, institutional, among others, since it is a multifaceted relationship.